Analisis kelayakan bisnis warkop bunda dalam memproduksi tape ketan hitam sebagai kudapan khas lebaran - Nadila Nadila; Rahmi Anugrah; Asmaul Husna; Fadhil Hidayat; Ichtiar Gunawan; Indah Nuraeni Mansyur (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2023)
The feasibility analysis of the Warkop Bunda Business in producing black sticky rice as a typical Eid snack is an activity carried out to measure the opportunities for future business success, this will be a benchmark whether the business is feasible to run or not, whether this business has sustainable opportunities or not. will stop operating when it has reached a certain point in time. In this era there is a standardization set to make something analyzed can be said to be feasible or not, the same as the aspects taken in this research used in several business feasibility studies including; in terms of market and marketing, in terms of risk anticipation, and technical aspects. Furthermore, the method used in collecting information data is a qualitative method by conducting direct interviews with sources. The final result of the research is that Warkop Bunda's business in producing Black Sticky Tape is feasible and has promising business prospects.